2015
DOI: 10.1177/1933719115585144
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Lysyl Oxidase Expression in Lesions and Endometrium of Women With Endometriosis

Abstract: This study documents that expression of LOX is differentially regulated in endometriotic lesions and endometrium. A role for LOX in mediating proliferation, migration, and invasion of endometrial and endometriotic cells was observed, which may be implicated in the establishment and progression of endometriotic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 84 publications
(105 reference statements)
0
26
0
Order By: Relevance
“…MMP-2 promotes angiogenesis during endometriosis progression via the cyclooxygenase (COX)-2/PGE2/pAKT axis (104). The upregulation of lysyl oxidase (LOX) expression is involved in extracellular membrane degradation, invasive and metastatic potential of endometriosis (105). The disruption of epithelialstromal communication networks elicits a feed-forward loop involving endometriosis to drive inflammation, which may be relevant in diseases such as EAOC.…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…MMP-2 promotes angiogenesis during endometriosis progression via the cyclooxygenase (COX)-2/PGE2/pAKT axis (104). The upregulation of lysyl oxidase (LOX) expression is involved in extracellular membrane degradation, invasive and metastatic potential of endometriosis (105). The disruption of epithelialstromal communication networks elicits a feed-forward loop involving endometriosis to drive inflammation, which may be relevant in diseases such as EAOC.…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…Moreover, previous studies have shown that LOX plays a crucial role in mediating proliferation, migration, and invasion by endometrial and endometriotic cells. Specifically, LOX influences the expression of genes related to fibrosis and ECM remodeling, including E-cadherin [6], which is indicative of its pro-metastatic potential. A recent study by Thomas et al [7] showed that LOX induces pre-metastatic bone lesions in breast cancer patients (especially ER– subgroup) by disrupting normal bone homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Our results in mouse uterus showed specific localization of Lox in the stromal cells surrounding the implanting embryos and the decidual cells during decidualization. High level of Lox expression is observed in the stromal cells in the endometrium of fertile women during WOI . The spatio‐temporally specific localization suggests the importance of Lox‐induced ECM remodeling during early pregnancy.…”
Section: Discussionmentioning
confidence: 96%